Complex realities : the impact of parental psychopathological disorders on the child-parent attachment through two case studies - Charot, Marie (My University, 2024)
This dissertation addresses the complex issue of attachment in parents with psychopathology, through the analysis of two different case studies. Its main objective is to explore the impact of psychopathological disorders on the quality of parent-child attachment. A literature review was carried out focusing on the effects of a specific psychopathological disorder on the parent-child bond, highlighting the observable manifestations of the bond and the possible disturbances resulting from the psychopathological condition. The results of this analysis provided an in-depth insight into how these parents manage to establish and maintain emotional bonds with their children, despite the challenges inherent in their mental health condition. The two case studies provide a more nuanced understanding of this complex relationship and were analyzed using the systemic model. The conclusions drawn from this research contribute to a better understanding of family dynamics, guidelines for early intervention or the development of policies and support programs, useful for mental health professionals, social workers and researchers working in the field of parenting and psychopathology.

Nesta dissertação aborda-se o complexo tema da vinculação em pais com psicopatologia, através da análise de dois estudos de caso distintos. O seu principal objetivo é explorar o impacto das perturbações psicopatológicas na qualidade da vinculação pais-filhos. Foi realizada uma revisão de literatura focada nos efeitos de uma perturbação psicopatológica específica na ligação pais-filhos, destacando as manifestações observáveis da ligação e as possíveis perturbações resultantes da condição psicopatológica. Os resultados desta análise forneceram uma visão aprofundada sobre a forma como estes pais conseguem estabelecer e manter laços afectivos com os seus filhos, apesar dos desafios inerentes à sua condição de saúde mental. Os dois estudos de caso fornecem uma compreensão mais matizada desta relação complexa e foram analisados tendo por base o modelo sistémico. As conclusões retiradas desta investigação contribuem para a melhor compreensão da dinâmica familiar, para orientações que visam a intervenção precoce ou para o desenvolvimento de políticas e de programas de apoio, úteis para profissionais de saúde mental, assistentes sociais e investigadores que trabalham no domínio da parentalidade e da psicopatologia.

Cette thèse aborde la question complexe de l'attachement chez les parents atteints de psychopathologie en analysant deux études de cas différentes. Son objectif principal est d'explorer l'impact des troubles psychopathologiques sur la qualité de l'attachement parent-enfant. Une revue de la littérature a été réalisée sur les effets d'un trouble psychopathologique spécifique sur l'attachement parent-enfant, en mettant en évidence les manifestations observables de l'attachement et les perturbations possibles résultant de l'état psychopathologique. Les résultats de cette analyse ont permis de comprendre comment ces parents parviennent à établir et à maintenir des liens affectifs avec leurs enfants, malgré les difficultés inhérentes à leur état de santé mentale. Les deux études de cas permettent une compréhension plus nuancée de cette relation complexe et ont été analysées à l'aide du modèle systémique. Les conclusions tirées de cette recherche contribuent à une meilleure compréhension des dynamiques familiales, des lignes directrices pour une intervention précoce ou le développement de politiques et de programmes de soutien, utiles pour les professionnels de la santé mentale, les travailleurs sociaux et les chercheurs travaillant dans le domaine de la parentalité et de la psychopathologie.
Dissertação para obtenção do grau de Mestre no Instituto Universitário Egas Moniz
Keywords: Quality of attachment; Parents; Psychopathology; Systemic model; Child protection